Immunology of the Lower Respiratory Tract: FUNCTIONAL PROPERTIES OF BRONCHOALVEOLAR LYMPHOCYTES OBTAINED FROM THE NORMAL CANINE LUNG - Kaltreider, H. B. (1973)
While the alveolar macrophage has been studied extensively, little attention has been directed toward the immune functions of the bronchoalveolar lymphocyte. These cells, obtained by bronchopulmonary lavage of the normal canine lung, are derived from the air side of the alveolar-capillary membrane of the lower respiratory tract. The distribution of lymphocyte types within the bronchoalveolar cell population was determined and compared with that of leukocytes from blood and spleen. IgG synthesis in vitro was used as a measure of bone marrow-derived lymphocyte (B cell) function, and the blastogenic response of cell cultures to phytohemagglutinin was used as a measure of the presence or absence of thymus-dependent lymphocytes (T cells). De novo synthesis of IgG by bronchoalveolar cells was demonstrated consistently by two independent radio-immunoassays. Therefore, B cells are present in the air spaces of normal canine lungs. T cells were generally not detectable in aliquots of the same cell populations but could be recruited into alveolar spaces after local irritation. The distribution of lymphocyte types within the bronchoalveolar cell population is unique and distinctly different from that of blood and spleen. The spleen is rich in both T cells and B cells, blood is rich in T cells but poor in B cells, whereas the lung lacks T cells and contains substantial numbers of immunoglobulin-producing B cells. The findings indicate that bronchoalveolar lymphocytes do not reflect simply the lymphoid composition of peripheral blood.